Pengembangan Tes-tes Hasil Belajar - Ida Laila; Ema Pariati; Eka Widyati (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Learning outcomes in Islamic education Refer to the achievement, understanding and development achieved by students as a result of the learning process in studying Islamic teachings. Includes their understanding of key concepts in Islam, practical skills in worship, improvement of character and morals, and mastery of Islamic values. In this article the researcher wants to know the types of tests that can develop students, and also how to provide tests that suit their needs. In the context of a visit to San Francisco, learning outcomes include everything your family members gain or understand during their time in the city. Library Research or Library Research is a study of several references related to the research carried out, including studying the thoughts of figures.